Career anchors and employee retention-an empirical study of Indian IT industry - Kannabiran, G. (Institute of Electrical and Electronics Engineers Inc., 2014)
Profound changes occurring in the occupational environment have implications for an individual's career development in the Indian IT industry. Organizations need to understand individuals' career anchors and be responsive to improve the employees' intention to stay. The present empirical study attempts to evaluate the impact of nine career anchors on employee's intention to stay through a survey of 450 employees among top Indian IT companies. It is found that the career anchors service, identity, variety, autonomy, creativity and geographic security have significant influence on the employees' intention to stay. However, other career anchors, namely, managerial competence, technical competence, and organizational stability have no influence on the employees' intention to stay. Â© 2014 IEEE.